Administrative management in procurement processes in a public sector entity - Asca Agama , Pompeyo Gabriel; Ramos Huamán, Olga María del Carmen; Espinoza Casco, Roque Juan; Espinoza Gálvez, Rogelio (Journal of business and entrepreneurial studie, 2021)
The objective of this work was to investigate the implications of administrative management in the procurement processes in a public sector entity, with a qualitative approach, the design was a case study, interviews were conducted using structured interview guides, the results of which will allow authorities and officials to implement corrective measures so that administrative management and procurement processes are done efficiently and transparently. The results showed that there was no interrelation between the phases of administrative management, deadlines were not met, the directives or manuals are outdated, there is a lack of monitoring of their processes and oversight, in order to achieve the goals set by the entity in a timely manner.